Should we teach physics? - Vladimir.B. Yassinskiy (Высшее образование в России)
The article discusses the problems of fundamental bachelor’s training with majors inengineering. The current educational system is not suited to create well-rounded professionals, who are capable of quick retraining when necessary. The author suggests ways of resolving these issues in teaching physics.